Implementasi Google Sites terhadap Motivasi Belajar Siswa Kelas VIII SMPN 1 Polongbangkeng Utara pada Mata Pelajaran IPA - Firmansyah, Muhammad Arham; Syam, Deby Febrianti; Kurniawan, Edy; Suriati, Suriati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The rapid advancement of technology has significantly impacted the field of education, making learning more interactive and engaging. This study aims to investigate the implementation of Google Sites in enhancing the learning motivation of eighth-grade students at SMPN 1 Polongbangkeng Utara in science subjects. The research employed a Classroom Action Research (PTK) approach with a quantitative descriptive method, involving 32 students as participants. Data were collected through observations, questionnaires, and documentation over two cycles of learning interventions. The results showed that students’ learning motivation increased progressively from the pre-cycle, with a low average of 38%, to cycle I with 55% (moderate), and reached 78% (high) in cycle II. Indicators such as diligence, perseverance, attention, achievement, and independence showed significant improvement after utilizing Google Sites. These findings suggest that Google Sites, as an interactive and easily accessible digital learning media, can effectively stimulate student engagement, facilitate understanding of complex concepts, and foster independent learning. The study highlights the potential of integrating technology-based media to enhance motivation in science education.